"Let your hair down" A. V. H. Hartendorp the man and his works - Canseco, Anicia G. (1974)
This paper contains a listing of the works of Abram Van Heyningen Hartendorp, published and unpublished, selected on the basis of their research value as Filipiniana materials. This includes books, articles, correspondence, essays, poems, and editorials, the latter, forming the greater bulk of this paper. It seeks to focus the significant contributions of Hartendorp in the fields of Philippine history, education, science, literature, culture (arts and music), politics and government, and economics.